Transcranial Direct Current Stimulation to Provide Neuroprotection and Enhance Cerebral Blood Flow in Stroke: A Comprehensive Review - Muhammed Enes Gunduz; Melike Kocahasan; Zafer Keser (Medicina)
Stroke remains a leading cause of global disability and mortality despite advancements in acute interventions. Transcranial direct current stimulation (tDCS), a non-invasive neuromodulation technique, has primarily been studied for its effects on cortical excitability, with limited exploration of its neuroprotective and hemodynamic benefits. This review examines the role of tDCS in stroke, with a focus on neuroprotection in acute settings and cerebral blood flow (CBF) modulation in both acute and chronic phases. tDCS offers rapid, localized delivery to salvageable ischemic tissue, exerting pleiotropic effects that address a broader spectrum of pathological processes compared to pharmacological agents. Cathodal tDCS shows promise in acute ischemic stroke for neuroprotection in small-scale clinical studies, enhancing CBF and promoting vessel recanalization, while anodal tDCS demonstrates stronger effects on CBF, particularly in chronic stroke and hypoperfusion cases. Bihemispheric stimulation may offer additional benefits, with evidence suggesting a dose-dependent relationship between stimulation parameters and therapeutic outcomes. Further research is warranted to optimize stimulation protocols, evaluate safety and feasibility, and explore the potential of tDCS to promote neuroplasticity and functional recovery across different stroke populations and stages. By addressing these gaps, tDCS could emerge as a valuable adjunctive therapy in stroke management, complementing current interventions and expanding therapeutic windows.